On-line fresh-cut lettuce quality measurement system using hyperspectral imaging. (April 2017) - Mo, Changyeun; Kim, Giyoung; Kim, Moon S.; Lim, Jongguk; Lee, Kangjin; Lee, Wang-Hee; Cho, Byoung-Kwan
Abstract : In this study, an online quality measurement system for detecting foreign substances on fresh-cut lettuce was developed using hyperspectral reflectance imaging. The online detection system with a single hyperspectral camera in the range of 400–1000 nm was able to detect contaminants on both surfaces of fresh-cut lettuce. Algorithms were developed for this system to detect contaminants such as slugs and worms. The optimal wavebands for discriminating between contaminants and sound lettuce as well as between contaminants and the conveyor belt were investigated using the one-way analysis of variance (ANOVA) method. The subtraction imaging (SI) algorithm to classify slugs resulted in a classification accuracy of 97.5%, sensitivity of 98.0%, and specificity of 97.0%. The ratio imaging (RI) algorithm to discriminate worms achieved classification accuracy, sensitivity, and specificity rates of 99.5%, 100.0%, and 99.0%, respectively. The overall results suggest that the online quality measurement system using hyperspectral reflectance imaging can potentially be used to simultaneously discriminate foreign substances on fresh-cut lettuces. Highlights: We developed online fresh-cut lettuce quality measurement system. The online measurement system was capable to detect defects on both surfaces of fresh-cut lettuce. The multispectral imaging algorithms were developed to detect the foreign substances. The imaging algorithms for slug and worm achieved the accuracy of 97.5% and 99.5%, respectively.